A bacteriological and pathological investigation of tuberculosis meningitis in the Western Province of the Cape of Good Hope. - Coetzee, Jack Nicol (Division of Chemical Pathology, 2014)
Although there have always been sporadic reports of spontaneous cures in tuberculous meningitis, up to a few years ago this diagnosis almost invariably meant death within a few weeks or months. The therapeutic use of Streptomycin in this disease has created new hope for these patients and has stimulated tremendous interest in all aspects of the disease.